The Effect of Centrifugal Force in Quantification of Colorectal Cancer-Related mRNA in Plasma Using Targeted Sequencing - Xue, Vivian Weiwen; Ng, Simon Siu Man; Leung, Wing Wa; Ma, Brigette Buig Yue; Cho, William Chi Shing; Au, Thomas Chi Chuen; Yu, Allen Chi Shing; Tsang, Hin Fung Andy; Wong, Sze Chuen Cesar (Frontiers in Genetics, 2018)
In our previous study, we detected the effects of centrifugal forces on plasma RNA quantification by quantitative reverse transcription PCR. The aims of this study were to perform targeted mRNA sequencing and data analysis in healthy donors’ plasma prepared by two centrifugation protocols and to investigate the effects of centrifugal forces on plasma mRNA quality and quantity. Targeted mRNA sequencing was performed using a custom panel with 108 colorectal cancer related genes in 18 healthy donors’ plasma that prepared by 1) 3,500g for 10 minutes at 4°C and 2) 1,600g for 10 minutes at 4°C followed by 16,000g for 10 minutes at 4°C. Results showed that plasma ribosomal RNA was detected in 16/18 (88.9%) 3,500g and 6/18 (33.3%) 1,600g followed by 16,000g centrifuged plasma. For targeted sequencing, 75/108 (69.4%) and 86/108 (79.6%) genes were detected in 3,500g and 1,600g followed by 16,000g, respectively, while 16/108 (14.8%) genes were not detected in both centrifugations. Detailed analysis showed that 2 of 108 (1.85%) genes showed lower expressions in 3,500g than in 1,600g followed by 16,000g. The median expressions of genes in 3,500g were positively correlated with the expressions in 1,600g followed by 16,000g (R2 = 0.9471, P < 0.0001, Spearman rank correlation). Meanwhile, plasma samples were not distinctively clustered based on centrifugal forces according to hierarchical clustering. Targeted mRNA sequencing and subsequent data analysis were performed in this study to investigate the effects of two different centrifugal forces that are commonly used in plasma collection. Our targeted sequencing results help to understand the centrifugal force effects on plasma mRNA, and these findings show that the centrifugation protocol for plasma mRNA research using targeted sequencing can be standardized which facilitates multicenter studies for comparison and quality assurance in future.